Exfoliation in a low boiling point solvent and electrochemical applications of MoO3 - Sricharan, Matangi; Gupta, Bikesh; Moolayadukkam, Sreejesh; Matte, H. S. S. Ramakrishna (Beilstein Journal of Nanotechnology, 2020)
MoO3 is a versatile two-dimensional transition metal oxide having applications in areas such as energy storage devices, electronic devices and catalysis. To efficiently utilize the properties of MoO3 arising from its two-dimensional nature exfoliation is necessary. In this work, the exfoliation of MoO3 is carried out in 2-butanone for the first time. The achieved concentration of the dispersion is about 0.57 mg·mL−1 with a yield of 5.7%, which are the highest values reported to date. These high values of concentration and yield can be attributed to a favorable matching of energies involved in exfoliation and stabilization of MoO3 nanosheets in 2-butanone. Interestingly, the MoO3 dispersion in 2-butanone retains its intrinsic nature even after exposure to sunlight for 24 h. The composites of MoO3 nanosheets were used as an electrode material for supercapacitors and showed a high specific capacitance of 201 F·g−1 in a three-electrode configuration at a scan rate of 50 mV·s−1.
Keywords: 2-butanone; liquid-phase exfoliation; low-boiling point solvent; molybdenum trioxide (MoO3); supercapacitors